Broadening the repertoire of functional herpes simplex virus type 1 (HSV-1)-specific CD8+ T cells reduces viral reactivation from latency in sensory ganglia() - St. Leger, Anthony J (2013)
A large proportion of the world population harbors herpes simplex virus type 1 (HSV-1) in a latent state in their trigeminal ganglia (TG). TG-resident CD8(+) T cells appear important for preventing HSV-1 reactivation from latency and recurrent herpetic disease. In C57BL/6J mice half of these cells are specific for an immunodominant epitope on HSV-1 glycoprotein B while the other half are specific for 18 subdominant epitopes. Here, we show that the CD8(+) T cell dominance hierarchy in the TG established during acute infection is maintained during latency. However, CD8(+) T cells specific for subdominant epitopes lose functionality while those specific for the immunodominant epitope exhibit increased functionality in latently infected TG. Furthermore, we show that IL-10 produced by 16.4 ± 2.8% of TG-resident CD4(+) T cells maintains the immunodominance hierarchy in part through selective inhibition of subdominant CD8(+) T cell proliferation. Upon systemic anti-IL-10 receptor antibody treatment, we observed a significant expansion of functional subdominant CD8(+) T cells, resulting in significantly improved protection from viral reactivation. In fact, systemic anti-IL-10 receptor antibody treatment prevented viral reactivation in up to 50% of treated mice. Our results not only demonstrate that HSV-1 reactivation from latency can be prevented by expanding the repertoire of functional TG-resident CD8(+) T cells, but also that IL-10 receptor blockade might have therapeutic potential to reduce or eliminate recurrent herpetic disease.